Induced basal normoglycemia and altered platelet aggregation in non-insulin-dependent diabetes. - Evans, R; Lane, J; Holman, R; Turner, R (1982)
Non-insulin-dependent diabetic subjects had abnormally raised in vitro platelet aggregation rates to collagen or ristocetin when thought to be "well-controlled" on diet alone but shown to have raised basal plasma glucose levels. Basal normoglycemia, induced with either ultralente insulin or chlorpropamide, was associated with a significant reduction of the enhanced platelet aggregation rates to normal. Some sulfonylurea drugs have been reported to have specific anti-platelet aggregatory properties, but the degree of plasma glucose control is probably more relevant.